BFENet: A two-stream interaction CNN method for multi-label ophthalmic diseases classification with bilateral fundus images. (June 2022) - Ou, Xingyuan; Gao, Li; Quan, Xiongwen; Zhang, Han; Yang, Jinglong; Li, Wei
Highlights: We propose a two-stream interactive CNN architecture for multi-label ophthalmic diseases classification with bilateral fundus images. We design a feature enhancement module by using the attention mechanism to learn the interdependence between local and global information, which enhances the extracted feature under the two-stream interactive architecture. A multiscale module is designed to enriches the feature maps by superimposing feature information of different resolutions images extracted through dilated convolution. Abstract: Background and objective: Early fundus screening and timely treatment of ophthalmology diseases can effectively prevent blindness. Previous studies just focus on fundus images of single eye without utilizing the useful relevant information of the left and right eyes. While clinical ophthalmologists usually use binocular fundus images to help ocular disease diagnosis. Besides, previous works usually target only one ocular diseases at a time. Considering the importance of patient-level bilateral eye diagnosis and multi-label ophthalmic diseases classification, we propose a bilateral feature enhancement network (BFENet) to address the above two problems. Methods: We propose a two-stream interactive CNN architecture for multi-label ophthalmic diseases classification with bilateral fundus images. Firstly, we design a feature enhancement module, which makes use of the interaction between bilateral fundus images to strengthen the extracted feature information. Specifically, attention mechanism is used to learn the interdependence between local and global information in the designed interactive architecture for two-stream, which leads to the reweighting of these features, and recover more details. In order to capture more disease characteristics, we further design a novel multiscale module, which enriches the feature maps by superimposing feature information of different resolutions images extracted through dilated convolution. Results: In the off-site set, the Kappa, F1, AUC and Final score are 0.535, 0.892, 0.912 and 0.780, respectively. In the on-site set, the Kappa, F1, AUC and Final score are 0.513, 0.886, 0.903 and 0.767 respectively. Comparing with existing methods, BFENet achieves the best classification performance. Conclusions: Comprehensive experiments are conducted to demonstrate the effectiveness of this proposed model. Besides, our method can be extended to similar tasks where the correlation between different images is important.